COLOSTRUM PRODUCTION, CALF BIRTH WEIGHT, AND POSTPARTUM OVARIAN FOLLICULAR ACTIVITY OF DAIRY COWS FED RESTRICTED DIET WITH DIFFERENT PROTEIN LEVELS DURING THE PREPARTUM PERIOD - M. U. Akhtar; Hifzulrahman; M. Ahmed; T. N. Pasha; M. Abdullah; R. M. Shahbakht; M. I. Haq; M. N. Haque (Journal of Animal and Plant Sciences, 2022)
Prepartum carry-over nutritional effects on postpartum reproductive performance result from complex interactions of many dietary variables, most importantly energy and protein. Thirty-six multiparous Holstein cows were blocked at −21 day relative to expected calving and randomly assigned one of the four treatments until calving: high (HMP) or low dietary metabolizable protein (LMP) with ad libitum (AFI) or restricted feed intake (RFI). The supplies of MP were 65 and 90 g/kg of DM for LMP and HMP diets, whereas intake was controlled to achieve 100 and 160% of NRC (2001) energy requirements for RFI and AFI groups, respectively. All the cows were fed a similar lactation diet after calving. Calving ease score and total number of ovarian follicles tended to increase in RFI versus AFI cows. The interaction between MP × intake indicated that calf birth weight tended to increase in RFI versus AFI cows when fed HMP versus LMP diet during the prepartum period. The day of first heat, calving to conception interval, and services per conception were not affected by prepartum dietary treatments. In conclusion, RFI versus AFI cows had easier calving, increased number of ovarian follicles, and higher calf birth weight, whereas HMP versus LMP diet increased size of small follicles and tended to increase size of large follicles.
Keywords: Periparturient cow; restricted energy; ovarian follicle; reproductive performance; calf birth weight